The pulmonary system during exercise in hypoxia and the cold - Sheel, A. W.; MacNutt, M. J.; Querido, J. S. (Experimental Physiology, 2010)
The demands for pulmonary O2 and CO2 transport in the exercising human are substantial. Fortunately, the regulatory and architectural limits of the pulmonary system meet the requirements of heavy exercise in most individuals. However, in some highly trained athletes the high metabolic demand of intense exercise is in excess of the capacity of the pulmonary system. Environmental considerations, in addition to those imposed by the demands of exercise, provide further physiological challenges that must be met. Winter athletes often encounter high-altitude hypoxia and cold, either transiently during competition or repeatedly during training. In this brief review, we examine the pulmonary system during acute and chronic exercise in hypoxic and cold environmental conditions. Observations from studies conducted in humans are emphasized in order to ask questions about regulation, plasticity and the limits of human physiology. We also highlight new findings and controversial questions that would benefit from additional study.